PENGARUH PROFESIONALISME DAN KOMPETENSI PENGAWASAN INTERNAL TERHADAP KUALITAS AUDIT PADA INSPEKTORAT PROVINSI BANTEN - Ulvia Fadilah; Eka Mahmudin S (FKIP, Universitas Banten Jaya, 2020)
This study aimed to examine the effect of professionalism and competence of internal supervision on audit quality at the Banten Provincial Government Inspectorate. This research developed a theoretical framework as a basis for hypotheses, to answer research questions consisting of how professionalism influences audit quality, and how competence influences audit quality. The samples of this study were 83 Government Internal Examiners (APIP) at the Inspectorate of Banten Province. This research used census method. The data used are primary data collected through questionnaires. Data analysis method to test hypotheses was Structural Equation Modeling (SEM) analysis using Partial Least Square (PLS). The results of this study indicate that: (1) professionalism hada positive and significant effect on audit quality, and (2) Competence had a positive and significant effect on audit quality.